Phage-Inspired Artificial Peroxidases with Robust Sub–Nanometer Cluster Sites for Efficient Oral Biofilm Elimination and Dental Caries Prevention - Zhu, Huang; Wang, Ting; Gao, Shihuan; Geng, Wei; Ma, Tian; Cheng, Liang; Han, Xianglong; Deng, Jiuhong; Gao, Shanshan; Cheng, Chong (Nano-Micro Letters, 2026)
Dental caries, a highly prevalent oral disease, is primarily driven by pathogenic biofilms; however, current antimicrobials exhibit limited efficacy and poor specificity against cariogenic biofilms. Although nanobiocatalysts that can produce reactive oxygen species represent a promising alternative to conventional antimicrobials, most current designs fail to achieve robust bacterial interaction and exhibit insufficient disruption of biofilm integrity. To address these challenges, we report the de novo design of phage-inspired artificial peroxidases (IrNC@TiO2) featuring a robust sub-nanometer cluster site and urchin-like topography, which enables efficient oral biofilm elimination and dental caries prevention. Structural characterization confirmed that sub-nanometer Ir clusters are stably anchored to the TiO2 support via Ir–O coordination. Leveraging the robust enzymatic activity of Ir clusterzymes and the topological advantages of the spiky substrate, IrNC@TiO2 exhibits potent multi-enzyme mimetic activity, generating substantial amounts of ·O2− and HClO to effectively capture and eradicate planktonic Streptococcus mutans and suppress biofilm formation. In a caries model, IrNC@TiO2 significantly inhibited tooth surface biofilm development, prevented enamel demineralization, and reduced caries incidence. The material also demonstrated negligible cytotoxicity and outperformed conventional non-abrasive additives in tooth-whitening assays. This work introduces a robust and efficient ROS-generating platform for oral health care and proposes a promising solution for clinical caries prevention. Highlights: 1 The phage-inspired de novo design of the artificial peroxidase (IrNC@TiO2) features robust subnanometer cluster sites and a sea-urchin-like topography. 2 The potent enzymatic activity of Ir clusterzymes and the topological advantages of the spiky substrate endow IrNC@TiO2 with the ability to effectively capture and eradicate planktonic Streptococcus mutans while inhibiting biofilm formation. 3 IrNC@TiO2 can significantly inhibit tooth-surface biofilm development, prevent enamel demineralization, and reduce caries incidence in anticaries experiments.